2019
DOI: 10.1111/jfs.12755
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Salmonella enterica serovar Typhimurium and Cronobacter sakazakii biofilms from food contact surfaces through enzymatic catalysis

Abstract: Bacterial biofilms are highly difficult to control, hence significant economic resources have been allocated to develop strategies to eradicate them. This study evaluated the effect of an enzymatic treatment to be used as a cleaning product to control the presence of biofilms. Two different materials used in the food industry, polystyrene and stainless steel, were tested using Salmonella Typhimuirum and Cronobacter sakazakii. Biofilm formation was carried out by inoculating the surfaces with a standardized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Biofilms in the food processing environment are composed of multiple microorganisms, resulting in an EPS with a heterogenic composition [ 28 ]. Recently, it has been demonstrated that polysaccharides in biofilms developed by Gram-negative bacteria, such as alginic acid, are the main component of the EPS matrix [ 13 ]. For example, the EPS matrix of S. Typhimurium is mainly composed of aggregative fimbriae and extracellular polysaccharides (cellulose) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms in the food processing environment are composed of multiple microorganisms, resulting in an EPS with a heterogenic composition [ 28 ]. Recently, it has been demonstrated that polysaccharides in biofilms developed by Gram-negative bacteria, such as alginic acid, are the main component of the EPS matrix [ 13 ]. For example, the EPS matrix of S. Typhimurium is mainly composed of aggregative fimbriae and extracellular polysaccharides (cellulose) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disinfection is the application of physical methods (UV light, cold plasma, ultrasound, etc.) or chemical agents (biocides and antimicrobials) to cause damage to or kill microorganisms [ 13 ]. Nonetheless, the use of physical [ 14 ] or chemical methods [ 15 , 16 ] is not enough to remove and eradicate the microorganisms within the biofilm, because the EPS occludes them with antimicrobial agents, reducing the shear forces [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, bacteria may be resistant to conventional treatments. Therefore, there is a need to enhance the methods and consider new strategies due to bacterial resistance’s serious problem ( Ripolles-Avila et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial biofilms, including of C. sakazakii , are difficult to control because the biofilm provides protection for the bacteria in the film [ 7 ]. Therefore, in order to eradicate biofilms in the food industry, considerable economic resources have been spent in the development of strategies [ 55 ]. In this study, LC-EO significantly reduced the number of viable bacteria in biofilms formed by C. sakazakii ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%